2008
DOI: 10.1038/modpathol.2008.76
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the expression pattern of GPI transamidase complex subunits in human cancer

Abstract: The glycosylphosphatidylinositol transamidase complex (GPIT) consists of five subunits: PIG-U, PIG-T, GPAA1, PIG-S and GPI8, and is important in attaching GPI anchors to target proteins. On the basis of our previous reports incriminating PIG-U as an oncogene in bladder cancer and PIG-T and GPAA1 as oncogenes in breast cancer, we evaluated the expression pattern of the GPIT subunits in 19 different human cancers at both mRNA and protein levels. In general, our results demonstrate a more frequent expression of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 19 publications
0
45
1
Order By: Relevance
“…PIGU protein has been found to be upregulated in prostate cancer (Nagpal et al 2008). Indeed, the fact that we see no obvious change in PIGU expression in the fusion positive case when compared to the entire data set stands in contrast to the previous fusions that we identified.…”
Section: Discovery Of Non-ets Gene Fusions In Prostate Cancercontrasting
confidence: 54%
“…PIGU protein has been found to be upregulated in prostate cancer (Nagpal et al 2008). Indeed, the fact that we see no obvious change in PIGU expression in the fusion positive case when compared to the entire data set stands in contrast to the previous fusions that we identified.…”
Section: Discovery Of Non-ets Gene Fusions In Prostate Cancercontrasting
confidence: 54%
“…In an earlier study, we observed a low expression of PIGK protein in tumors compared to paired normal tissues of some CRC patients (11). We hypothesized that such low expression could be due to mutation in the coding regions of the PIGK gene.…”
Section: Distribution Of Snp 1048575 Among the Crc Patientsmentioning
confidence: 99%
“…However, the role of PIGK in tumorigenesis remains largely unknown. Recently, we reported a low expression of PIGK protein in some CRC, hepatocellular (HCC) and urothelial cell carcinoma (UCC) patients (11). We hypothesize that the altered expression of PIGK could be due to mutation in the coding regions of this gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several roles have been suggested for the GPI posttranslational modification apart from the membrane anchoring of proteins. Hence, GPI anchors may be involved in cell contact and adhesion and have a role in cellular communication, signal transduction, oncogenesis [18] and immune response [19]. Furthermore, this lipid modification has been shown to be relevant for prion disease pathogenesis and for parasites, which use the GPI anchor to increase their infectivity [15].…”
Section: Types Of Lipidation Glycosylphosphatidylinositol Anchor (Gpi)mentioning
confidence: 99%